Saturation Loadings on 13X (Faujasite) Zeolite above and below the Critical Conditions, Part I: Alkane Data Evaluation and Modeling - Al-Mousa, Alaa Marwan Subhi (2015)
The saturation loadings for subcritical adsorption of n-, iso- and neo alkanes C1 –C8 in 13X zeolite are modeled using the modified Rackett model of Spencer and Danner (1972) for the saturated liquid densities combined with crystallographic data for the 13X zeolite. For validation of this model, alkane adsorption data in the literature is first critically evaluated and then compared to the model. The saturation loading of each isotherm that approaches saturation is extracted from the data. Log-log plots are used to determine whether each isotherm is near saturation; isotherms that exhibit a [del]lnq⁄[del]lnp slope of zero at their maximum pressure point are assumed to be saturated. Isotherms not fulfilling this criterion are deemed unsaturated and not considered further. The theoretical equation satisfactorily models the available experimental data for the n- alkanes. However, steric factors are required for the model to fit iso alkanes and neo-pentane. For supercritical temperatures, no model presently exists to explain the data. However, the data are satisfactorily modeled with an equation of the form qmax = 8.5 ± 2.5 g/100 g.